Tectonic Evolution of Central Madurai Block, Southern India and Potential Heat Source for High-Temperature Metamorphism - Rashid, Janwari Shazia AB (2018)
The Madurai Block is the largest granulite block in Southern Granulite Terrain which lies between Palghat-Cauvary shear zone in the North and Achankovil shear zone in the South. This terrain underwent extreme crustal metamorphism under ultrahigh-temperature metamorphic conditions which provides vital information about the tectonic process of the lower crust. Ultrahigh temperature metamorphism was defined by Harley (1998b) as a subclass of granulite facies metamorphism of crustal rocks in which peak temperature exceeds 900°C at moderate pressures (7-13 kbar) in the deep crust. However, considering the lacunae about the present understanding of ultrahigh temperature metamorphism, the study attempts to identify the heat source and role of lower crustal fluids in high temperature metamorphism. To understand the role of lower crustal fluids, a case study on migmatised metapelites from the Kodaikanal region was done where the metapelites have undergone UHT metamorphism. In-situ electron microprobe Th-U-Pb isochron (CHIME) dating of monazites in a leucosome and surrounding silica saturated and silica under saturated restite from the same outcrop indicate three principal ages which can be linked in with the evolutionary history of these rocks. The monazite grains in leucosome sample show alteration along the rims. These altered rims are experimentally replicated in a monazite-leucosome experiment at 800°C and 200MPa. This experiment, coupled with earlier published monazite-fluid experiments involving high pH alkali-bearing fluids at high P-T, helps to confirm the idea that alkali-bearing fluids, in the melt and along grain boundaries during crystallization, were responsible for the formation of the altered monazite grain rims via the process of coupled dissolution-reprecipitation. Lower crustal fluids during migmatization and high temperature metamorphism from leucosome monazites signify the need for a more precise texturally-controlled geochronological determination. Considering the possible heat source of high temperature metamorphism, the role of associated rocks of charnockites/granites and ultramafics was studied from Kodaikanal and Ganguvarrpatti. The results indicate that both charnockites and granites are not the heat source of high temperature metamorphism. However, to recognize the ultramafic as the potential heat source the sapphirine-bearing high Mg-Opx bearing rock was studied from Kambam town. The sapphirine–cordierite intergrowth pods are characterized by unique texture and peraluminous sapphirine composition suggesting that these domains could represent cryptic pathways through which aluminous melts migrated. The mineral phase equilibria considerations suggest that such peraluminous melts interacted with Mg-rich orthopyroxene in the host granulite at 1025°C and 8 kbar, with subsequent isobaric cooling. The underplated mafic magma (T>1000°C) is suggested as a possible mechanism that provided the heat source for partial melting of lower crust and the UHT metamorphism. Moreover, field evidence of metapelite in direct contact with an ultramafic body was observed resulting into granulite grade metamorphism. The other evidence of ultramafic magma as heat source is though the mineral chemistry and geochemical modeling of the studied ultramafic rocks.